THE PRODUCTIVE ZAKAT UTILIZATION MODEL BY THE MAGELANG CITY BAZNAS ZAKAT INSTITUTION IN INCREASING MUSTAHIQ INCOME - Yunia Tri Lestari (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
The purpose of this study was to determine the optimization of the strategy and utilization of productive zakat by the Magelang city BAZNAS zakat institution in increasing Mustahiq income in the city of Magelang. The research methodology used is a qualitative approach, with a case study strategy. Data collection was carried out by interviewing the head of the human resources sector from Baznas of Magelang City, amil zakat, and three mustahiq recipients of productive zakat funds.  The analysis technique used is descriptive analysis. Based on the research results, it was found that productive utilization of zakat funds by BAZNAS zakat institutions in this case was channeled through seven superior programs. One of the programs in order to empower the community to improve their economy is the Capital Assistance program. This Capital Assistance Program, in which there is also a skill and skills training program, this program is a productive zakat utilization model by BAZNAS in increasing mustahiq income which according to researchers is already optimal. This is evidenced by an increase in mustahiq income, and the ability of mustahiq to become muzakki.